The Role of Stress Arousal in the Dynamics of the Stressor‐to‐Illness Process among Accountants* - SMITH, KENNETH J.; EVERLY, GEORGE S.; JOHNS, TONY R. (Contemporary Accounting Research, 1993)
Abstract. This study investigates the Kahn et al. (1964) measure of job‐related stressors, and the Everly et al. (1989) measure of stress (i.e., cognitive‐affective) arousal to ascertain whether the scales are measuring two distinct constructs. Data gathered from a sample of 1,618 members of the American Institute of Certified Public Accountants are analyzed to measure the psychometric properties of both instruments. Results from internal consistency, exploratory and confirmatory factor analyses, and item analyses indicate that both scales are reliable measures and the two scales are measuring different constructs, This study also examines the mediating effect of stress arousal on the relationship between sources of job stress, and resultant coping behaviors and psychological stress symptoms by means of structural modeling analyses. The results indicate that stress arousal is indeed a significant mediator in the stressor‐to‐illness process. Résumé. Les auteurs analysent l'instrument de mesure utilisé par Kahn et al. (1964) pour évaluer les facteurs de stress liés au travail ainsi que la mesure de la manifestation (cognitive‐affective) du stress proposée par Everly et al. (1989) pour confirmer si les échelles utilisées circonscrivent deux concepts distincts. Ils analysent les données colligées à partir d'un échantillon de 1 618 membres de l'American Institute of Certified Public Accountants afin d'évaluer les propriétés psychométriques des deux instruments de mesure. Les résultats tirés des analyses des facteurs de cohérence interne, des facteurs exploratoires et des facteurs de corroboration, ainsi que les analyses des éléments indiquent que les deux échelles de mesure sont fiables et qu'elles circonscrivent des concepts différents. Les auteurs examinent également l'effet de médiation de la manifestation du stress sur la relation entre les sources de stress au travail et les comportements d'adaptation qui en résultent et les symptômes de stress psychologique, au moyen d'analyses de modélisation des structures. Les résultats de l'étude indiquent que la manifestation du stress est, de fait, un médiateur d'importance dans le processus qui conduit du facteur de stress à la maladie.